From substantive pluralism to procedural pluralism: a proposal beyond analytical questions for Portuguese- speaking African realities (Passagens: Revista Internacional de História Política e Cultura Jurídica, 2025)
At first, the approach of this article is linked to the various concepts of legal pluralism, which illustrate the theoretical differences between high and low density, weak and strong, independent and autonomous, prescriptive and descriptive pluralism. On the other hand, the article seeks to understand the manifestation of legal and sociological pluralism, which in Africa has a strict relationship with the models of colonial domination that were present in Portuguese and English-speaking countries, in which certain models conditioned the regression of the recognition of the normative plurality of these states, through a colonial positive theory, imposed without assessing the sociological and cultural framework of the African peoples. Finally, the article presents a conception of an adjective pluralism, also known as procedural pluralism, which involves a series of structures for the formation of an institutional and procedural plurality that is capable of maintaining links with functional elements of the traditional justice system, with the aim of a systemic and peaceful dialogue that feeds back into the formal state system, especially in the jurisdictional sphere.